Effects of Marijuana Use on Smokers Switching to E-Cigarettes in a Randomized Clinical Trial. Issue 7 (11th January 2022) - Rice, Myra; Nollen, Nicole L; Ahluwalia, Jasjit S; Benowitz, Neal; Woodcock, Anna; Pulvers, Kim
Abstract: Introduction: Co-use of tobacco and marijuana is common, and research suggests that marijuana use may be a barrier to smoking cessation. Research to date has not evaluated how marijuana use affects e-cigarette switching behaviors and related outcomes in a harm reduction trial. Aims and Methods: This secondary analysis includes African American (48%) and Latinx (52%) adult smokers randomized to the e-cigarette group ( N = 114) of a harm reduction clinical trial from 2018 to 2019. Participants were provided JUUL e-cigarettes and encouraged to make an exclusive switch for 6 weeks. Our primary outcome was cigarettes smoked per week. Secondary health outcomes were e-cigarette substitution (calculated by measuring e-cigarette pod use), expired carbon monoxide (CO), and respiratory symptoms. Marijuana products were recorded at three timepoints and coded for combustion. Results: Marijuana use during the study ( n = 52, 46%) was not associated with week 6 cigarettes smoked or e-cigarette substitution, and combustible marijuana use was not associated with week 6 respiratory symptoms ( p s > .05). After controlling for cigarettes smoked at week 6, combustible marijuana use was significantly associated with a 4.4 ppm increase in CO compared with no use of marijuana ( p = .001). Conclusions: Marijuana use was not a barrier to switching to e-cigarettes in this 6-week trial. Marijuana use contributed to elevated CO, reflecting greater exposure to toxic combustion products, beyond the effects of cigarette smoking. Marijuana co-use may increase risk of adverse health outcomes and may be a confounding factor when using CO as an endpoint to bioverify exclusive e-cigarette use. Implications: This is the first known study to examine the effects of marijuana use on smokers switching to e-cigarettes. Marijuana use was not a barrier to cigarette reduction in a 6-week randomized clinical trial. Marijuana use uniquely contributed to higher carbon monoxide among cigarette smokers, indicating greater exposure to toxic combustion products, which could increase risk of adverse health outcomes. Furthermore, combustible marijuana use may be a confounding factor when CO is used as an endpoint to bioverify exclusive e-cigarette use.